Hubungan Dukungan Orang Tua pada Kesehatan Gigi Mulut Anak dan Status Kebersihan Mulut - Vonny N. S. Wowor; Ni Wayan Mariati; Militia J. Kalalo (e-GiGi, 2024)
Abstract: Children's behavior towards oral and dental health is influenced by the support and attitude of parents, especially the ability of parents to educate children about the awareness of the importance of oral and dental health to children. Active role of parents in the form of information, instrument and appreciation support is highly important to overcome children's oral and dental health problems and improve the children’s oral and dental health. This study aimed to determine parental support for children's oral and dental health as well as the oral hygiene status of children, and to evaluate the relationship between parental support for children's oral and dental health and children's oral hygiene status. This was a descriptive and analytical study with a cross-sectional design using total sampling, namely the children in grades 1–6  at SD GMIM 85 Wori of 97 and their parents. Data were collected using a parental support questionnaire on children's oral dental health and examination of children's oral hygiene status. The results showed that measuring parental support was based on information, instrument, and award support of 97 respondents obtained an average score of 4788 in good category and the child's oral hygiene status was in the moderate category (56.7%). The chi-square test obtained a p-value of 0.001 (p <0.05). In conclusion, there is a significant relationship between parental support for children's oral and dental health and oral hygiene status. Keywords: parental support; oral hygiene status; behavior of elementary school children   Abstrak: Perilaku anak terhadap kesehatan gigi dan mulut dipengaruhi oleh dukungan dan sikap orang tua, terutama kemampuan orang tua untuk menanamkan sikap peduli dan sadar akan pentingnya kesehatan gigi dan mulut kepada anak. Peran aktif dari orang tua berupa dukungan informasi, instrumen, dan penghargaan sangat penting untuk mengatasi masalah kesehatan gigi mulut dan peningkatan derajat kesehatan gigi mulut pada anak. Penelitian ini bertujuan untuk mengetahui hubungan dukungan orang tua pada kesehatan gigi mulut anak dengan status kebersihan mulut anak. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang, menggunakan total sampling  anak kelas 1–6  SD GMIM 85 Wori berjumlah 97 responden beserta orang tuanya. Pengumpulan data menggunakan kuesioner dukungan orang tua terhadap kesehatan gigi mulut anak dan pemeriksaan status kebersihan mulut anak. Hasil penelitian ini merupakan pengukuran dukungan orang tua berdasarkan dukungan informasi, dukungan instrumen dan dukungan penghargaan, mendapatkan skor rerata 4788 dengan kategori baik dan status kebersihan gigi mulut anak sebagian besar (56,7%) dengan kategori sedang. Uji chi-square mendapatkan nilai p=0,001 (p<0,05). Simpulan penelitian ini ialah terdapat hubungan antara dukungan orang tua pada kesehatan gigi mulut anak dengan status kebersihan mulut anak. Kata kunci: dukungan orang tua; status kebersihan mulut; perilaku anak sekolah dasar